A study of the effectiveness of implementing e-commerce and social media websites to cater Malaysia Airlines (MAS) international market / Murni Shuhada Ibrahim - Ibrahim, Murni Shuhada (Faculty of Business and Management, 2010)
E-commerce now has become a more popular strategy of marketing efforts, besides the traditional marketing effort done by organizations in order to reach out and gain from the advantages provided by E-commerce. E-commerce combines traditional and electronic marketing to create a more vast business opportunities and capture a larger number of audiences towards one’s business. When it comes to online social networking, websites are commonly used. These websites are known as social sites. Social networking websites function like an online community of internet users. Depending on the website in question, many of these online community members share common interests in hobbies, religion, or politics. Most organizations that practice e-commerce nowadays are a sure user of such social media websites. The social media websites are a powerful marketing tool for organizations practicing e-commerce. Malaysia Airlines has leveraged all these technology that benefits the organization and public.